2020
DOI: 10.1016/j.jclepro.2019.119205
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the practices and roles of UK construction manufacturers and merchants in relation to housing energy retrofit

Abstract: This is a repository copy of Exploring the practices and roles of UK construction manufacturers and merchants in relation to housing energy retrofit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…By contrast, “technical skills” were unique to a particular actor group. The definition of technical skills, however, was in agreement with existing literature (Killip et al , 2020), where the skills were linked to a knowledge or understanding of a type of technology. For further comparison, the results indicated diverse ideas and meanings associated with the required skills by key actors.…”
Section: Discussionsupporting
confidence: 65%
“…By contrast, “technical skills” were unique to a particular actor group. The definition of technical skills, however, was in agreement with existing literature (Killip et al , 2020), where the skills were linked to a knowledge or understanding of a type of technology. For further comparison, the results indicated diverse ideas and meanings associated with the required skills by key actors.…”
Section: Discussionsupporting
confidence: 65%
“…Their opportunity for influence appears to be greater sideways and downstream than upstream. There is a particular need for trade professionals to upskill since they have a direct influence on the likely success of bottom-up change, such as that instigated by householders (Janda & Killip 2013;Janda et al 2014;Wilson et al 2013;Wade et al 2016aWade et al , 2017aSimpson 2017;Killip et al 2020). Middle actors naturally aggregate knowledge from one project to the next and learn from experience.…”
Section: Discussionmentioning
confidence: 99%
“…New collaborations and mutual learning between academia, training and multiple middle-actor parties in the industry could build capacity and enhance knowledge development for creating and maintaining a zero-carbon built environment. The progression to zero carbon requires that technologies and strategies be deployed at pace and with POE to evaluate physical performance continually (Killip et al 2020) and to ensure occupant satisfaction with the deployed products and design strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has explored the middle-out requirements for building professionals acting within this space (Janda and Parag, 2012;Owen et al, 2020). To deliver desired outcomes from sustainable renovation, Killip et al (2020) suggested an approach to include routine postoccupancy monitoring of sustainable renovation projects to inform future work.…”
Section: Construction Training and Sustainabilitymentioning
confidence: 99%